Impact of the Financial Crisis on Social Services Financing and Delivery - Virginia S. Pineda (Philippine Institute for Development Studies (PIDS), 1999)
National leadership over the past three decades has recognized regional development as an important policy thrust and strategy for national development. Hence, regional allocation becomes an integral part in the national government budgeting system, which is aimed for greater efficiency and effectiveness. The practice of regional budgeting in the Philippines has started during the Marcos administration. Aquino government pursued a top-down bottom-up approach in the budgeting process. Ramos government continued the same approach but with less fervor. To aid the Ramos administration in its achievement of regional development as a means to achieve the goals national government's end, this paper assesses regional budget allocation in terms of process and responsiveness to the diverse regional social/economic conditions.
Keywords: 330; Asian financial crisis; services sector; Asian crisis; service delivery; social services